Analysis of the Influence of Rotor Coupling effect on Vibration of High Speed Angular Contact Ball Bearing - Ye Zhenhuan; Liu Zhansheng; Wang Liqin (Jixie chuandong)
Based on the displacement coupling relationship and loading equilibrium relationship between rolling bearings and rotor,a dynamics model of rolling bearings- rotor system based on the internal load- bearing deformation coordination condition is established. A pair of 276927NK1W1（ H） angular contact ball bearings in symmetry in the single- rotor system are used as the example,the influence of rotor coupling on vibration of angular contact ball bearings is analyzed,and the influence rule of working conditions of bearings on rotor coupling effect are future studied. The results could afford more accurately reference for failure analysis of high speed ball bearings.